Agri-Food Outlook 2025. - Alltech Alltech (Zernovì Produkti ì Kombìkorma)
After a stagnant 2023, global feed production rebounded in 2024, according to Alltech’s 2025 AgriFood Outlook, which estimates that feed production expanded by 16.7 million metric tons (mt) in 2024, an increase of 1.2%. This growth — achieved despite challenges such as highly pathogenic avian influenza (HPAI), climate fluctuations and economic uncertainty — underscores the resilience and adaptability of the international agriculture industry.